Gambaran Pola Konsumsi Pangan, Aktivitas Fisik dan Status Gizi Anak Sekolah Dasar di SDN Oebafok Kecamatan Rote Barat Daya Kabupaten Rote Ndao - Messakh, Devita Madelret; Nur, Marselinus Laga; Rahayu, Tanti; Aspatria, Utma (Universitas Respati Indonesia, 2025)
Food consumption of elementary school children needs to be considered because of their rapid growth, resulting in increased growth and activity. This study aims to determine the description of food consumption patterns, physical activity, and nutritional status of elementary school children at SDN Oebafok, Southwest Rote District, Rote Ndao Regency. This type of research is descriptive research using the total sampling technique method. The population in this study were grade IV, V, and VI students totaling 42 students. Data collection was conducted through interviews using research questionnaires namely 2x24 Hour Food Recall, Physical Activity Questioner for Children (PAQ-C), and Anthropometric Data. Data analysis used univariate analysis. The results showed that the food consumption of students at SDN Oebafok based on the type of food was mostly diverse (76.2%) and not diverse (23.8%). Based on the amount of energy intake, 52.4% of students had insufficient intake and 47.6% had good intake. Based on meal frequency, 64.3% of students had a low meal frequency and 35.7% had a good meal frequency. The majority of physical activity was moderate (54.8%), low (4.8%), and high (40.4%). The nutritional status of students was dominated by poor nutrition (38.1%) and obesity (2.4%). The need for nutrition education to students and education to teachers related to nutrition for school-age children, and monitoring of nutritional status to improve eating habits and nutritional status.